Predictor’s of Mortality in Patients with Aneurysmal Subarachnoid Haemorrhage and Reebleding - Dannys Rivero Rodríguez; Claudio Scherle Matamoros; Leda Fernández Cúe; Jose Luis Miranda Hernández; Yanelis Pernas Sánchez; Jesús Pérez Nellar (Neurology Research International)
Methods. “Ameijeiras Brother’s” and “Cmdt. Manuel Fajardo” Hospitals enrolled 64 patients (multicentre retrospective cohort) with aneurysmal subarachnoid haemorrhage and rebleeding. The patients were admitted to the Stroke Unit (SU) between January 1, 2006, and December 1, 2013. Demographic, clinical, and radiological variables were examined in logistic regression to evaluate independent factors for increasing the risk of death. Results. Patients with systolic blood pressure >160 mmHg (P=0.02), serum glucose >7 mmol/L (P=0.02), aneurysm location in artery communicant anterior (P=0.03), and black/mixed race (P=0.008) were significant related to death in univariate analysis. Risk factors (HTA, smoke, alcohol consumption, and DM), complication, multiplex rebleeding and stage of WFNS, and Fisher’s scale were not related to mortality. Patients with three or more complications had a higher mortality rate (P=0.002). The results of the multivariate logistic regression analysis indicated that race (black/mixed, P=0.00, OR 4.62, and 95% IC 1.40–16.26), systolic blood pressure (>160 mmHg, P=0.05, OR 2.54, and 95% IC 1.01–3.13), and serum glucose (>7.0 mmol/L, P=0.05, OR 1.82, and 95% IC 1.27–2.67) were independent risk factors for death. Conclusions. The black/mixed race, SBP, and serum glucose were independent predictors of mortality. Three or more complications were associated with increasing the probability to death. Further investigation is necessary to validate these findings.